Search for Therapeutic Agents for Cardiac Arrest Using a Drug Discovery Tool and Large-Scale Medical Information Database - Zamami, Yoshito; Niimura, Takahiro; Koyama, Toshihiro; Shigemi, Yuta; Izawa-Ishizawa, Yuki; Morita, Mizuki; Ohshima, Ayako; Harada, Keisaku; Imai, Toru; Hagiwara, Hiromi; Okada, Naoto; Goda, Mitsuhiro; et al. (Frontiers in Pharmacology, 2019)
The survival rate of patients with cardiac arrest is less than 10%; therefore, the development of a therapeutic drug that improves the prognosis of cardiac arrest patients is necessary. In this study, we searched for drugs that improve the survival rate of patients who had suffered cardiac arrest, using the information on cardiac arrest cases collected from medical facilities throughout the country. Candidate drugs that can improve the prognosis of patients with cardiac arrest were extracted using "TargetMine", a drug discovery tool. Next, we examined whether or not the candidate drugs were included in the drugs administered within 1 month after cardiac arrest, using cardiac arrest cases obtained from the Japan Medical Data Center. Furthermore, logistic regression analysis was performed with the explanatory variables being the presence or absence of the administration of those candidate drugs that were administered to 10 or more patients and the objective variable being the “survival discharge”. For drugs that are significantly related to survival discharge increase, adjusted odds ratio for survival discharge, excluding the influence of covariates such as patient's background, medical history and treatment factors, by IPTW method, using tendency score, was calculated. One hundred and sixty-five drugs with vasodilator activity were extracted by TargetMine. Drugs not approved in Japan, oral medicines, and external medicines, were excluded. We checked whether the candidate drugs were administered to the 2227 patients with cardiac arrest, using the data obtained from the Japan Medical Data Center. The results of logistic regression analysis show that 3 (isosorbide dinitrate, nitroglycerin, and nicardipine) out of 7 drugs that were administered to 10 or more patients showed significant association with survival discharge increase. When these drugs were analyzed in detail using propensity scores, the adjusted odds ratios for survival discharge in the isosorbide dinitrate, nitroglycerin, and nicardipine users were 3.35, 5.44, and 4.58, respectively. It is considered that isosorbide dinitrate, nitroglycerin, and nicardipine may be novel therapeutic agents that improve the prognosis of cardiac arrest patients, as significant survival rates are observed even at odds ratios adjusted for covariates using propensity scores.